تحليل فيلم سانغ فنجيراح من خلال المبادئ الإسلامية: وتطبيقها في حياة المجتمع بولاية يوكياكرتا: Sang Pencerah Films: Analysis of Islamic principles and their application in the life of the community in Yogyakarta - Muhamad, Octafa Nuha Zahra; Ahmad H. Osman , Rahmah; Nuryadin, Trian Ramadhan; Ainurrahman, Qurrota A’yun (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص لفيلم باعتباره وسيلة من وسائل الإعلام له دور مهم في الجوانب الاجتماعية والثقافية والفنية والسياسية والعلمية. كذلك يعتبر استخدام الأفلام في جهود التربية المجتمعية جزئا مهما على اعتبار أن الأفلام لديها القدرة على جذب انتباه المشاهدين، وتعتمد جزئيًا أيضا على سبب أن الأفلام لديها القدرة على توصيل الرسائل بطريقة فريدة (McQuail، 1994 :13). والأفلام تثير مجموعة من التأثيرات من شأنها أن تؤدي إلى تغييرات المجتمع في النهاية. إن تأثير الرسالة التي يحدثها الفيلم في الواقع الرمزي يشعر بها الجمهور مباشرة، ويمكن أن يكون في شكل تغييرات عاطفية، في هذه الدراسة يأخذ الباحث فيلماً يريد به تحليل بعض الآثار المجتمعية، ويعتبره مثالاً حقيقياً على أسلمة السينما في إندونيسيا. وهو فيلم " سانغ فنجيراح " يحكي عن كفاح رائد وطني وهو كياي الحاج أحمد دحلان. علاوة على ذلك أراد الباحث أن يكشف عن مبادئ الإسلام في هذا الفيلم وكيفية تطبيقها في حياة المجتمع. وتهدف الدراسة أيضا إلى معرفة المبادئ الإسلامية في الفيلم وآثارها في حياة المجتمع خاصة بولاية يوكياكرتا. وقد استخدم الباحث في هذ البحث نظرية السيميائية رولاند باثس. لأن هذا البحث هو البحث الأساسي في شكل نوعي. والطريقة المتبعة في هذه الدراسة هي الطريقة التاريخية. ومن نتائج هذا البحث أن الأفلام لها تأثير مهم، والأفلام لها دور كبير جدًا في المجتمع يمكن أن يغير حياته في المستقبل. وكذلك هناك الجوانب التي يمكن أن تؤخذ من هذا الفيلم والتي تؤثر أيضًا على حياة مجتمع يوكياكرتا بشكل خاص.وهذا التأثير من الناحية التربوية والعقدية والاجتماعية والدعوية. Abstract Film is a media that has an important role in the social, cultural, artistic, political and scientific world. The use of films in community education efforts is partly based on the consideration that films have the ability to hold viewers' attention and partly on why films have the ability to communicate messages in a unique way (McQuail, 1994:13). It can elicit a range of influences from its broadcast which ultimately leads to community changes. The effect of the message that occurs to the film in the packaging of symbolic reality is felt by the audience directly, and can be in the form of emotional changes. The researcher takes a film that he wants to analyze, and considers it a real example of the Islamization of cinema in Indonesia. The movie "Sang Pencerah" tells about the struggle of the national pioneer, Kiai Hajj Ahmad Dahlan. Moreover, the researcher wanted to reveal the principles of Islam and how to apply them in the life of society. And aimed to know the principles of Islam in the film and their effects on the life of the community, especially in the state of Yogyakarta. In this research, researcher used the semiotic theory Roland Baths. This research is basic research in a qualitative form. The method used in this study is the historical method. The results of this research are that films have an important impact and films have a very large role in society that can change their lives in the future. There are many aspects that can be taken from this movie that also affect the life of the Yogyakarta community, in terms of education, monotheism, social and da'wah.